The ASCRS Textbook of Colon and Rectal Surgery 2021
DOI: 10.1007/978-3-030-66049-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Construction

Abstract: Anastomotic construction represents a fundamental and essential skill restoring intestinal continuity and preserving bowel function and continence.• It encompasses a broad range of methods and configurations and can be performed utilizing a spectrum of operative platforms. • While anastomosis may be a heterogeneous endeavor, consistent fundamental principles must be preserved in all its forms. • Stapling technologies represent a challenge for surgeon knowledge and understanding their use in clinical practice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 90 publications
(124 reference statements)
0
13
0
Order By: Relevance
“…Several different features of hand sewn bowel anastomoses have been considered including suture material, continuous or interrupted suture, single or multilayer closures, and tension on the anastomosis. 1 A large systematic review of techniques for hand sewn colorectal anastomoses, including ileocolic anastomoses, concluded that “a single-layer continuous technique using inverting sutures with slowly absorbable monofilament material” was associated with lowest risk of postoperative complications. 2 One weakness of hand sewn anastomoses is a heavy dependence on the technical expertise of the surgeon and ability to reproduce results consistently.…”
Section: General Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several different features of hand sewn bowel anastomoses have been considered including suture material, continuous or interrupted suture, single or multilayer closures, and tension on the anastomosis. 1 A large systematic review of techniques for hand sewn colorectal anastomoses, including ileocolic anastomoses, concluded that “a single-layer continuous technique using inverting sutures with slowly absorbable monofilament material” was associated with lowest risk of postoperative complications. 2 One weakness of hand sewn anastomoses is a heavy dependence on the technical expertise of the surgeon and ability to reproduce results consistently.…”
Section: General Considerationsmentioning
confidence: 99%
“…Staplers not only rely on tissue compression and multiple rows of staples spaced to adequately seal the bowel but also allow for consistent perfusion. 1 While some early studies suggested that stapled anastomoses carried higher risk of anastomotic leak when compared with hand sewn techniques, 3 4 others have found decreased anastomotic leak rates in patients with stapled anastomoses. 5 6 A 2019 large multicenter study of over 4000 patients undergoing open right hemicolectomy found no significant difference in leak rates between patients with hand sewn and stapled ileocolic anastomoses.…”
Section: General Considerationsmentioning
confidence: 99%
See 3 more Smart Citations